Effects of Slow-release Urea vs conventional urea and Molasses on Digestibility, Rumen Fermentation, Nitrogen Balance and Microbial Protein yield in Sheep - Mashayekhi, MR; sari, mohsen; Jolazadeh, AR (Journal of the Hellenic Veterinary Medical Society, 2025)
The objectives of this study were to evaluate the effects of using a type of slow- release urea (SRU) and conventional feed grade urea (CFU) with or without molasses (MO) on the diets of growing sheep. An experiment was conducted by using 4 mature-male Lori sheep (24.7 ± 0.9 kg BW) cannulated in the rumen in a- 4×4 Latin-square design with a factorial arrangement of 2×2 to evaluate the effects of two main factors of urea sources (US) (feed-grade urea versus slow- release urea) and level of molasses (M) (0% versus 20%) on intake, nutrient digestibility, nitrogen retention, rumen fermentation, and microbial nitrogen in sheep. In addition, an in situ experiment was conducted to determine N disappearance of urea sources from polyester bags. The lambs were fed with 4 isonitrogenous and isocaloric diets consisting 70% concentrate and 30% sugar cane tops (DM basis) that were offered in two equal meals (08.00 and 20.00; 5 to 10 percent orts on an as-fed basis). The following treatments implicative of (UM0) feed-grade urea (16 g/kg DM) without molasses, (UM20) feed-grade urea (16 g/kg DM) with molasses (200 g/kg), (SM0) slow-release urea (18 g/kg DM) without molasses, and (SM20) slow-release urea (18 g/kg DM) with molasses (200 g/kg). Nutrient digestibility, nitrogen balance, total purine derivatives (PD( and estimated microbial protein synthesis were not different between the treatment groups although digestibility of OM tended to increase in 20% M supplemented groups (P= 0.057). Overall, the means of total VFA concentration and its proportions were not different (P> 0.05), but with the addition of molasses to the diets, the concentrations of propionate (P= 0.016) and butyrate (P= 0.024) decreased and increased, respectively. Ruminal pH, NH3–N, and plasma metabolites were not affected by the addition of US or M (P> 0.05). Significant effects of the sampling time on ruminal pH (P= 0.002), ruminal NH3–N (P<0.001), BUN, and plasma glucose (P<0.001) were observed. It could be concluded that the inclusion of M or US did not affect the feed intake, digestibility, blood metabolites, and generally, most of the ruminal fermentation parameters after evaluation; but, more research is required to evaluate their uses in diets.